Impacts of Climate Change on Dengue Haemorrhagic Fever Cases in Banjarbaru Municipal, South Kalimantan During the Year 2005-2010 - Tien Zubaidah (Center for Journal Management and Publication, 2013)
Environment is one of instrumental factor in the emerging and the spreading of dengue disease. The Climate change may causes affect to infectious disease pattern and the risk of transmission increasement. Disease of dengue hemorrhagic fever (DHF) has become endemic in the major cities in Indonesia. It has been suspected that dengue outbreaks that occur each year in almost all of Indonesia is closely related to weather patterns. The purpose of this study was to determine the influence of climate change (rainfall, humidity and air temperature) with dengue cases in the Banjarbaru municipal during the year 2005-2010. The design of the study is a over times studies of ecology. The research was conducted in April-May 2010 and located in the Banjarbaru municipal, South Kalimantan by using secondary data. Data on the number of dengue cases was derived from the Banjarbaru Health Office reports. Climate data used are rainfall data, temperature and humidity obtained from the Meteorology and Geophysics Board (BMKG) Station of Banjarbaru and Syamsudin Noor Station of Banjarmasin. The results showed that rainfall, humidity, air temperature and free number larva had influence toward insidence of DHF (27%). The conclusion of this study is that the increased rainfall and humidity affected the increased in dengue cases. Therefore, it requires a good cooperation between the health department and BMKG as the party in charge for climates data.Â